Design and implementation of high frequency induction heating with LLC resonant load matching using ELTA - Suganthi Karuppusamy; Sunandhitha V; Suraj R; Roja T S; Sundararaman K (Institute of Advanced Engineering and Science, 2020)
Induction heating is a non-contact method of producing heat which can be used to perform various processes like hardening, annealing, tempering, welding, brazing, melting, forging, etc. This paper discusses the design and implementation of induction heating on a given work-piece, using an LLC resonant circuit and a transformer for impedance matching, so as to transfer a maximum power of 5KW to the load. The load parameters are found out using ELTA software which calculates the values based on the dimensions of the work piece, operating frequency and temperature. The inverter used is based on SiC MOSFETs which minimizes the losses at high frequencies and high temperatures. The theoretical and simulated results from MATLAB are analysed and verified. The hardware is implemented for the LLC circuit with transformer and the results are presented.